The duality as the main principle of representation of character system in M. Houellebecq’s novels «Whatever» and «The Elementary Particles» - Дерев’янченко, Наталя Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article is devoted to the features of organization of character system of Michel Houellebecq’s novels «Whatever» and «The Elementary Particles». It is noted that the motive of duality is dominant in the representation of characters. The antagonist pares were defined (“against the world” / “in the middle of the world” or an observer / a doer). Antagonism manifests itself in the fact that one of the members of the pair is a passive observer, and the other is a doer, an active fighter for survival in the modern world. The heroes represent the opposition of the passive beginning in a man and the rebellious, embodying different, but at the same time, complementary tendencies that characterize an individual at the end of the twentieth century. It was mentioned that Michel Houellebecq uses minor characters for intensification of the duality idea. The system of characters is marked by the impossibility of division into positive and negative and ambivalence is always emphasized. No member of the pair attains happiness because it is unattainable, regardless of whether one is a passive observer or tries to struggle for survival. Antagonist characters who express the extreme degree of a particular idea or life stance come into a dialogic conflict, but the issues raised in it remain open. This method of representation of character system enables the writer to make the idea of uncertainty and instability of «I» in cultural identity of a modern European. The motive of duality is connected with carnival world view, which is inherent in the novel-menippea.